Implementation of Sharia Insurance in providing Sustainable Finansial Protection - Syamsuri, Helmy; Muin, Rahmawati; Abdullah, Muhammad Wahyuddin (Technium Sustainability, 2024)
Sharia insurance is essential in providing sustainable financial protection for individuals and communities. By adhering to the principles of Islamic Sharia, Islamic insurance offers financial protection in accordance with religious values while promoting shared prosperity and sustainable risk management. This research uses a library research method with data collection carried out in several stages, from collecting references to analyzing references relevant to this research. In contrast, data sources are obtained from literature reviews from books, journals, the internet, and other media. This article outlines the general background of Islamic insurance and the importance of financial protection and explains the fundamental differences between conventional insurance and other insurance. In addition, the article discusses the long-term benefits to society at large. A better understanding of the role of Islamic insurance in providing sustainable financial protection is expected to strengthen the overall Islamic financial system and offer significant benefits to individuals and society. Shariah insurance focuses on meeting financial needs and adherence to moral and ethical principles in Islam. This insurance firmly holds principles: ta’awunu ’ala al birr wa al-taqwa (help you all in goodness and piety) and al-ta’min (security).